2013
DOI: 10.3810/pgm.2013.09.2706
|View full text |Cite
|
Sign up to set email alerts
|

Weight Considerations in Psychotropic Drug Prescribing and Switching

Abstract: Our review describes potential weight-altering effects of psychotropic medications (antipsychotics, antidepressants, anti-anxiety medications, mood stabilizers, sedative-hypnotics, medications for attention-deficit/hyperactivity disorder, and other psychotropic medications) and offers guidance on switching a medication if its weight-altering effect becomes problematic. For second-generation antipsychotics, the risk of weight gain is high with clozapine and olanzapine, low with amisulpride, aripiprazole, and zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 94 publications
1
48
1
2
Order By: Relevance
“…However in our study we found evidence for an association between mental disorders and weight gain independent of smoking, alcohol consumption, physical activity and social activity, which was in line with recent prospective studies that adjusted for lifestyle (Brumpton et al, 2013;Singh et al, 2014;Lasserre et al, 2014). The use of psychotropic medication has been suggested as a confounding factor in the association between psychopathology and weight change since medication use has shown to interact with mechanisms regulating food intake and appetite (Virk et al, 2004;Demyttenaere and Jaspers, 2008;Papakostas, 2008;Vieweg et al, 2008;Hasnain and Vieweg, 2013). Initially we found in a subsample of our study with persons having a current depressive and anxiety disorders that SSRI users as well as benzodiazepine users compared to non-users were more likely to gain weight.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However in our study we found evidence for an association between mental disorders and weight gain independent of smoking, alcohol consumption, physical activity and social activity, which was in line with recent prospective studies that adjusted for lifestyle (Brumpton et al, 2013;Singh et al, 2014;Lasserre et al, 2014). The use of psychotropic medication has been suggested as a confounding factor in the association between psychopathology and weight change since medication use has shown to interact with mechanisms regulating food intake and appetite (Virk et al, 2004;Demyttenaere and Jaspers, 2008;Papakostas, 2008;Vieweg et al, 2008;Hasnain and Vieweg, 2013). Initially we found in a subsample of our study with persons having a current depressive and anxiety disorders that SSRI users as well as benzodiazepine users compared to non-users were more likely to gain weight.…”
Section: Discussionsupporting
confidence: 77%
“…However, the found effects for SSRI use seemed to be mainly driven by the severity of the depressive symptoms. Surprisingly, the effect of benzodiazepine use on weight gain remained borderline significant after full adjustment, which is conflicting with previous research which found that benzodiazepine use was weight neutral (Vieweg et al, 2008;Hasnain and Vieweg, 2013). Other explaining mechanisms for the association between mental disorders and subsequent weight increase are physiological abnormalities found in depressed persons such as increased inflammation, and longterm disturbances of the HPA-axis.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In addition, there were concerns about further weight gain on mirtazapine in an already obese adolescent. 26 Increasing risperidone, considering its effect on hypersexual behaviors as mentioned above, was one of the options in our patient; however, this was dismissed after discussion of possibility of worsening metabolic side effects and weight gain. Sexual dysfunction is a known side effect of β-blockers, including propranolol.…”
Section: Discussionmentioning
confidence: 79%
“…We investigated the percentage body weight change during treatment with an antipsychotic and/or a MS that has been associated with a high-medium risk of weight gain [48]. Patients treated for at least five consecutive visits with a SGAP (olanzapine, clozapine, quetiapine or risperidone) or a MS (lithium or valproate) were selected.…”
Section: Investigated Phenotypes and Outcomesmentioning
confidence: 99%